THE APPLICATION OF FUZZY DELPHI METHOD IN DESIGN AND DEVELOPMENT OF ENGLISH-SPEAKING SKILLS FORMATIVE ASSESSMENT TOOL FOR STUDENTS WITH AUTISM SPECTRUM DISORDER (ASD) - Amal Mohamad Hassan; Low Hui Min, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Communication in children with Autism Spectrum Disorder (ASD) is often significantly impacted by various neuropsychological and psychological challenges, which also affect their behavior and social interactions. These challenges manifest in various ways, including difficulties in understanding and using verbal and non-verbal communication, interpreting social cues, and engaging in reciprocal social interactions. One of the primary challenges faced by children with ASD is their difficulty in communicating effectively. This barrier makes it hard for them to convey their needs, thoughts, and emotions, often leading to frustration and impacting their ability to form meaningful connections with others. The inability to express themselves clearly not only complicates their interpersonal relationships but also limits their interaction with their environment. Given these communication difficulties, developing effective strategies to enhance the English-speaking skills of students with ASD becomes crucial. This study focuses on the design and development of formative assessments tool of English-speaking skills using the application of Fuzzy Delphi Method (FDM). This tool is integrated with the project-based learning (PBL) approach, which immerses students in real-world tasks aimed at cultivating critical thinking, creativity, and problem-solving skills. Ten experts are involved in designing and developing the contents of the instruments, rubric and performance descriptors which are the main elements of the formative assessment tool. This formative assessment tool, specifically designed for students with ASD, offers continuous feedback, enabling educators to modify their teaching methods according to the unique needs of each student for better learning outcomes.